SUSTAINABILITY REPORT DISCLOSURE EVALUATION BASED ON GLOBAL REPORTING INITIATIVE (GRI) STANDARD (A Case Study at PT PLN (PERSERO) 2017-2019) - Hapsari, Swasti Woro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This study aims to analyze the disclosure of Corporate Social Responsibility (CSR) activities in the Sustainability Report of PT PLN (Persero) in 2017-2019 based on the Global Reporting Initiative (GRI) Standard. This study employed a qualitative approach by using secondary data. The results of this study indicate that PT (PLN) Persero has implemented the GRI Standard in the preparation of its sustainability report, although not all topics are disclosed. PT PLN (Persero)'s universal standard disclosure level was 64% in 2017, 59% in 2018, and 61% in 2019. Overall, the disclosure level for company-specific topics was 30% in 2017, 26% in 2018, and 34% in 2019. Specific topics consist of economic, social, and environmental categories. The level of disclosure in the economic category in 2017 and 2018 was 54% each, while it was 62% in 2019. The disclosure rate for the environmental category in 2017 and 2018 was 17% respectively and increased to 27% in 2019. Moreover, the level of social category disclosure in 2017, 2018, and 2019 was 30%, 26%, and 34%, respectively. It can be concluded that the level of disclosure of economic categories is consistently higher than the level of disclosure of the other two categories.Keywords: Corporate Social Responsibility, Global Reporting Initiative (GRI) Standard, Sustainability Report